Modulation of Macrophage Immunometabolism: A New Approach to Fight Infections - Gauthier, Thierry; Chen, Wanjun (Frontiers in Immunology, 2022)
Macrophages are essential innate immune cells that contribute to host defense during infection. An important feature of macrophages is their ability to respond to extracellular cues and to adopt different phenotypes and functions in response to these stimuli. The evidence accumulated in the last decade has highlighted the crucial role of metabolism reprogramming during macrophage activation in infectious context. Thus, understanding and manipulation of macrophage immunometabolism during infection could be of interest to develop therapeutic strategies. In this review, we focus on 5 major metabolic pathways including glycolysis, pentose phosphate pathway, fatty acid oxidation and synthesis, tricarboxylic acid cycle and amino acid metabolism and discuss how they sustain and regulate macrophage immune function in response to parasitic, bacterial and viral infections as well as trained immunity. At the end, we assess whether some drugs including those used in clinic and in development can target macrophage immunometabolism for potential therapy during infection with an emphasis on SARS-CoV2 infection.